2017
DOI: 10.1097/hrp.0000000000000137
|View full text |Cite
|
Sign up to set email alerts
|

How Well Do We Understand the Long-Term Health Implications of Childhood Bullying?

Abstract: Once dismissed as an innocuous experience of childhood, bullying is now recognized as having significant psychological effects, particularly with chronic exposure. Victims of bullying are at risk for a number of psychiatric disturbances, and growing evidence suggests that the pathophysiological effects of bullying, as with other forms of trauma and chronic stress, create additional health risks. We review the literature on the known sequelae of bullying, including psychiatric and physiological health effects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 91 publications
0
34
0
Order By: Relevance
“…35 The academic achievement of students may fall as a consequence of bullying, and they may feel the effects of bullying even during adulthood. 35,36 Our third finding is that victims, bullies, and bullyvictims have more suicidal thoughts than respectively non-victims, non-bullies and the students that did not involve in bullying cycle. In an eleven-month follow-up study, both bullies and victims were at a higher risk of suicide and selfharm behaviors.…”
Section: Discussionmentioning
confidence: 76%
“…35 The academic achievement of students may fall as a consequence of bullying, and they may feel the effects of bullying even during adulthood. 35,36 Our third finding is that victims, bullies, and bullyvictims have more suicidal thoughts than respectively non-victims, non-bullies and the students that did not involve in bullying cycle. In an eleven-month follow-up study, both bullies and victims were at a higher risk of suicide and selfharm behaviors.…”
Section: Discussionmentioning
confidence: 76%
“…Chronic stress, defined as a situation in which the body faces numerous challenges every day, has shown to be one of the most dangerous situations for the maintenance of homeostasis, due to allostatic overload [6,31]. In particular, daily challenges from bullying pose a threat to allostasis (a set of processes that allow organisms to maintain homeostasis while adapting to the demands of the environment) [32].…”
Section: Discussionmentioning
confidence: 99%
“…This complex phenomenon has been increasing dramatically across the world over recent years [2] with an estimated prevalence of 36% according to a recent meta-analysis [3]. Bullying victimization has shown to have severe negative consequences for the health and quality of life of bullied adolescents, such as higher levels of depression, anxiety, somatic symptoms, and suicidal ideation [4,5,6]. In line with this, a recent study conducted with 6667 students concluded that being bullied has a significant negative impact on physical, psychological, and social domains of quality of life [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…School bullying is associated with severe mental health problems, learning difficulties and dropping out of school; it has both short-term and long-lasting negative effects (Arseneault et al, 2010;Tan et al, 2017;Zarate-Garza et al, 2017). It may also increase the risk of suicide among students (Mossige et al, 2016).…”
Section: Introductionmentioning
confidence: 99%